La luz del intelecto agente en los principios de la razón práctica según San Alberto Magno - Rego, Thomas (Sapientia, 2008)
Sophocles’ Antigone and the Corpus Hippocraticum describe the proper features of natural law. Aristotle's Ethics, then, offers an explicit notion of natural law, which St. Albert comments in Super Ethica. However, in Cicero's De inventione the German theologian finds his natural law's definition: “what certain innate strength inserted”. In De bono V q. 1, St. Albert establishes the length of this definition and presents a complete notion of natural law. St. Albert also notices that man, in relation to the practical intellect's science, is twice in potency. Firstly, he is in potency of knowing the first principles of this science, and, secondly, once they are known, he is in potency of inferring from them the conclusions of the practical science. When he possesses these conclusions, finally, he is in potency of applying them in practical life. Intrigued by the way in which these first principles are known, St. Albert realizes that the knowledge of the notions corresponding to these principles only accidentally must be attributed to the discovery or determination of the names, with which we call these principles. In truth, is necessary that the light of agent intellect intervene to conduct the knowledge of the principles to the act. In this point, St. Albert discourse returns to Cicero's definition: that innate strength which inserts natural law is not other than the light of the agent intellect.